Circulating economic geographies: citation patterns and citation behaviour in economic geography, 1982?2006 - Christopher Muellerleile (Transactions of the Institute of British Geographers, 2007)
The paper presents a citation analysis of articles published in economic geography (broadly defined) in the period since the 1980s, with a supplementary analysis of significant books in the field. The overwhelmingly Anglocentric character of ‘international’ economic geography is reaffirmed, as both journal publishing and the citation ‘market’ are dominated by authors from the UK, US and Canada. There is some evidence, however, that the field is beginning to internationalize, just as there are also indications that the reach of economic geography, qua‘exporter’, is extending into other parts of the social sciences.